THE FOUNDATION OF SURDOPEDAGOGY IN UZBEKISTAN’S HIGHER EDUCATION SYSTEM - Abdullayeva Nargiza Oktamovna (Bright Mind Publishing, 2025)
This teaching-methodical manual is written for teachers within the special education system and general education schools with inclusive education programs, focusing on the educational challenges faced by deaf and hard-of-hearing children. It offers an in-depth description of Uzbek sign language and the structured system for its instruction.
Keywords: Sound-based language, deaf-mute women of some Caucasian peoples prohibited from speaking with sounds, World Federation of the Deaf.